Persepsi Mahasiswa terhadap Perkembangan dan Penggunaan Teknologi pada Lingkungan - Aria Indah Susanti (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
elements in the ecology of learning itself. Therefore, the activeness of students in following technological developments should be utilized to support a more innovative and adaptive learning environment. This study was conducted to see students' perceptions of the development and use of technology, especially the impact of technology on the surrounding environment and learning environment. The approach used in this study is a quantitative approach with a descriptive research type. This research was conducted in the Faculty of Tarbiyah, State Islamic Institute of Madura. The sampling technique used was Simple Random Sampling. The data collection techniques used by the researcher were distributing questionnaires and interviews. The results of the study showed that students' perceptions of the development and use of technology in the environment showed that students understood technology and its development well and its use in the environment, especially the learning environment. Students as active users of technology (especially smartphones and the internet) have a positive perception of the development and use of technology in the learning environment.